Simmered Then Boiled: Multi-Decadal Poleward Shift in Distribution by a Temperate Fish Accelerates During Marine Heatwave - Smith, Kimberley A.; Dowling, Christopher E.; Brown, Joshua (Frontiers in Marine Science, 2019)
Sillago schomburgkii inhabits coastal waters of south-western Australia, where it occurs over a wide latitudinal range (22-35 S). The species has occupied this range for at least the past century. It is a valuable fishery species, particularly in northern (warmer) areas where it has historically been most abundant. Fishery trends indicate a gradual poleward shift in the centre of abundance since the 1950s, coinciding with gradual ocean warming over the same period. This shift dramatically accelerated after the 2010/11 marine heatwave, when abundance abruptly declined at the northern edge of the range but increased in southern areas. The heatwave drew attention to the significant, but previously unrecognised, distributional shift of S. schomburgkii. It also helped to elucidate the recruitment-related mechanism by which the shift is occurring. There was evidence of exceptionally strong recruitment by the 2010/11 year class in southern areas, but weaker recruitment at the northern edge. Spawning by S. schomburgkii is associated with ocean temperatures of approximately 20-26 C. Temperatures are in this range for most of the year in the north, but only briefly during the height of summer in the south. During the heatwave, coastal temperatures were up to 5 degrees above average. It is likely that the spawning period was reduced in the north but extended in the south, due to higher temperatures, which would explain the recruitment trends in each area. All evidence suggests the distributional shift is primarily due to altered spawning success by resident fish in each area (i.e. self-recruitment), rather than by the movement of adults or larval dispersal. The accelerated shift during the heatwave was probably due to major changes in self-recruitment, but possibly supplemented by atypical southwards larval dispersal. For commercial and recreational fisheries that capture this species, the ongoing poleward range shift could have significant negative and positive impacts in the northern and southern areas, respectively. Fisheries in southern areas are expected to benefit from an increasing availability of this species, although a predicted climate-induced loss of critical habitats could negate any gains at the southern edge of the range.